Enhanced lasing action in Cr:forsterite laser using temporally separated pump pulses. (July 2022) - Sahoo, Siba Prasad; Pradhan, Swarupananda; Mukherjee, Jaya; Rawat, V.S.
Highlights: The output energy of Cr:forsterite laser is doubled using temporally separated pumping (TSP) configuration. The TSP configuration circumvents the ground state depletion of Cr 4+ dopants and the excited-state absorption (ESA) effect. The use of a polarization-based laser resonator eliminates the requirement variable optical delay between pump pulses. A rate-equation-based model is developed to study the associated mechanisms and to validate the experimental observations. This technique will help in reducing the probability of damage to the crystal, and adverse thermal effects in the crystal. Abstract: The depletion of the ground state population and increase in the excited-state absorption (ESA) limit the efficiency of a gain-switched solid-state laser at higher pump pulse energies. We have circumvented these shortcomings by using temporally separated dual pump pulses instead of a single pump pulse of higher energy. The second pump pulse re-pumps the ground state population accumulated during the buildup time of the laser pulse, leading to enhanced lasing action. The temporally separated pumping (TSP) configuration reduces the ESA effect at higher pump pulse energies and boosts the laser output energy. The TSP configuration has the inherent advantage of reducing the thermal effects as the pump pulse energy is temporally distributed. It allows pumping the crystal at higher cumulative pump pulse energy than the single pumping (SP) configuration. We have demonstrated the TSP configuration in a gain-switched Cr:forsterite laser using a polarization-based laser resonator cavity. The output energy of the laser is increased by a factor of two in the TSP configuration, compared with the conventional SP configuration using the same pump pulse energy. The polarization-based resonator cavity is suitable for optimization of the TSP configuration as the cavity buildup time can be tuned continuously while maintaining a constant delay between the two pump pulses. We have used a rate-equation-based model to study the associated mechanism in consistency with the experimental observations.